OPAC 2000, a new pavement design system - He, Zhiwei (University of Waterloo, 1997)
Pavement management exists at two basic levels: network and project. The network level is concerned with determining maintenance and rehabilitation needs and developing programs for new pavement construction for various sections within overall budget constraints. The project level deals with acquiring and analysing data from those sections designated for action at the network level, carrying out the structural design and associated economic evaluation, and implementation in terms of construction and periodic maintenance and rehabilitation. The basic objective of pavement design is to provide feasible structural alternatives with optimal service lives which minimize total life cycle costs. This is achieved by generating a series of design alternatives, performing structural and economic analyses and providing the results in an organised format, which provides the basis for the decision-making at the project level. OPAC 2000 is a new pavement design package, which handles the pavement design process in a comprehensive computerized system. The system was developed at the University of Waterloo under a contract with the Ministry of Transportation of Ontario. This thesis provides the procedures and the background engineering principles used in the development of the system. The following tasks were carried out. First, the existing OPAC was evaluated in light of both the requirements of a computerized pavement design system and the special needs of the system users. Second, some of the available major pavement design systems were reviewed in terms of their design methodologies, computer package availability, advantages and disadvantages. The third task was collecting pavement structure, performance history, subgrade and traffic data from in-service pavements on the Ontario highway network, from which a new set of pavement performance prediction models were established. Fourth, a new economic analysis module was developed based on the most recent Ontario and international studies. Fifth, a comprehensive system design was developed, which specified details of each design module, input and output requirements as well as the logic connections among the modules. The key enhancements and innovations in OPAC 2000, compared to the existing OPAC system, include: 1. A new set of flexible pavement performance models, 2. Capability of carrying out overlay designs, 3. Capability of carrying out reliability analysis, 4. Capability of carrying out rigid pavement design including overlay designs, by employing the AASHTO rigid pavement design equation, 5. A new, improved and more comprehensive economic analysis module, 6. Capacity of estimating impacts to environment due to pavement works, 7. Use of the MS WindowsTM-based computing environment, 8. A versatile, comprehensive and "user-friendly" software package (in SI units), and 9. Demonstration of how the OPAC 2000 performance models could be used to extend the system to network level pavement management. This thesis provides the procedures, equations and the related background engineering principles that were used in the development of the system. The following conclusions are based on the study: 1. The mechanistic-empirical nature of the OPAC pavement design method is retained in the OPAC 2000 pavement design system, 2. The OPAC pavement performance prediction model is updated based on in-service pavement performance data .Two separate models are developed based on cluster analysis: one for Southern Ontario, and one for Northern Ontario, 3. A systematic methodology was used in developing OPAC 2000 as a fully functional self-contained pavement design package, 4. A project level pavement design system should be considered within the scope of an overall pavement management system. Although OPAC 2000 was developed for the province of Ontario, the engineering principles, the techniques and the methodology used in developing the system are believed to be transferable to other regions. Through appropriate model calibrations, OPAC 20000 type of systems could be readily adapted to such other regions.
Keywords: Harvested from Collections Canada